Community Empowerment During the Covid 19 Pandemic, Through Assistance for Vulnerable Communities (Interprofessional Collaboration/Interprofessional Education Approach) - Hery Sumasto; Teta Puji Rahayu; Suparji Suparji; Nurwening Tyas Wisnu; Syaifuddin Syaifuddin; Hupitoyo Hupitoyo; Yuyun Setyorini (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
This community empowerment activity is carried out in the form of mentoring for the people of Bedagung Village, Panekan District, Magetan Regency, East Java. The people of Bedagung Village, Panekan District, Magetan Regency, are very anxious and afraid of the ferocity of the Covid-19 Non-Natural Disaster. Besides they face natural disasters of landslides and cyclones every year, they are currently facing the ferocity of the Covid 19 pandemic. Bedagung village is located on the slopes of a mountain so it is very prone to natural disasters, landslides. Based on these problems, the role of academics is needed to improve preparedness and Disaster Risk Reduction, through community empowerment. Community empowerment is very much needed through the assistance of Interprofession Collaboration (IPC) and Interprofession Education (IPE) approaches with Disaster Mitigation And Training (DMT). The purpose of empowering community assistance is to realize a Healthy Village through preparedness and disaster risk reduction in dealing with the threat of natural disasters and non-natural disasters (Covid-19). Methods to achieve the goal with the Golden Triangle, namely: 1) apply research and expertise; 2) build university cooperation; 3) apply IPC and IPE from 5 (five) professions, namely the profession of Midwife, Nurse, Electromedical Engineering, Environmental Health and management science. Parties involved in this activity: 1) Magetan Regency Government; 2) Bedagung Village Government; 3) Community health center; 4) Disaster Preparedness Village Team; and 5) Regional Disaster Management Agency. Activities carried out to achieve the objectives include: 1) classical material; 2) field practice; 3) follow-up implementation. The time for empowerment activities is 6 months. Outputs: 1) Journal publications; 2) publication through mass media; 3) Intellectual Property Rights; 4) update the Village Disaster Risk map; 5) the establishment of a Destanasif Task Force (Comprehensive Disaster Resilient Village); 6) have a Volunteer certificate and a trainer certificate; 7) training module with ISBN.